Therapeutic Drug Monitoring of Tigecycline in 67 Infected Patients and a Population Pharmacokinetics/Microbiological Evaluation of A. baumannii Study - Yang, Tianli; Mei, Hekun; Wang, Jin; Cai, Yun (Frontiers in Microbiology, 2021)
Background: The wide-spread use of antibiotics has led to the emergence of multidrug-resistant (MDR) bacteria such as multidrug-resistant Acinetobacter baumannii (AB). Tigecycline (TGC), as the first glycylcycline antibiotic approved by FDA, is a broad-spectrum antibiotic which remains highly effective to treat AB infections. Objective: To confirm the TGC treatment dosage and effectiveness to treat AB infections in Chinese population by performing therapeutic drug monitoring (TDM). Methods: This study was performed from Oct. 2018 through Mar. 2019 at the PLA General Hospital. A high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) method was validated and employed to determine the plasma concentrations of TGC in patients with infectious diseases. The minimum inhibitory concentration (MIC) of TGC to clinically isolated AB was determined by broth microdilution method, agar dilution method and disk diffusion method. Moreover, a model of population pharmacokinetics/pharmacodynamics (PPK/PD) was constructed. Results: A total of 186 plasma samples from 67 patients were detected by validated HPLC-MS/MS method. The MIC values determined by the broth microdilution method were more sensitive and accurate than the other two methods. The microbial and clinical PK/PD breakpoints were reached when the maintenance dose of TGC was 100 mg. Conclusions: Our study established a validated HPLC-MS/MS method to monitor the plasma concentrations of TGC. In view of the MIC range to AB isolates in our hospital and the PPK/PD modeling results, we recommend a relatively high dose of 100 mg q12h regimen to achieve the optimal clinical efficacy and antimicrobial response.